The pressures and opportunities for coral reef preservation and restoration in the Maldives - Hilmi, Nathalie; Basu, Ritu; Crisóstomo, Matías; Lebleu, Lara; Claudet, Joachim; Seveso, Davide (Frontiers in Environmental Economics, 2023)
The ocean plays a fundamental role in the human well-being and development. Therefore, it is vital to preserve and restore the marine ecosystem services that are being damage through climate change and anthropic activities, even more in countries such as the Maldives that has been classified under a high degree of exposure and vulnerability. The purpose of this article is to provide an overview of the problems facing coral reefs in the Maldives through relevant scientific insights; outline the importance of reef conservation in this area, given their ecosystem services; and briefly discuss policies and mitigation plans for reef conservation in the Maldives against anthropic activities and climate change, including potential funding sources and how best to engage with local communities and other stakeholders in this effort. This will help to achieve several SDGs.